Periodic Solutions for a Class of n-th Order Functional Differential Equations. (10th October 2011) - Song, Bing; Pan, Lijun; Cao, Jinde
Abstract : We study the existence of periodic solutions for n -th order functional differential equationsx ( n ) ( t ) = ∑ i = 0 n − 1 b i [ x ( i ) ( t ) ] k + f ( x ( t − τ ( t ) ) ) + p ( t ) . Some new results on the existence of periodic solutions of the equations are obtained. Our approach is based on the coincidence degree theory of Mawhin.